Effects of long-term treatment with the luteinizing hormone-releasing hormone (LHRH) agonist Decapeptyl and the LHRH antagonist Cetrorelix on the levels of pituitary LHRH receptors and their mRNA expression in rats - Horvath, Judit E. (National Academy of Sciences, 2002)
The effects of depot formulations of the luteinizing hormone-releasing hormone (LHRH) agonist Decapeptyl (25 μg/day) for 30 days or LHRH antagonist Cetrorelix pamoate (100 μg/day) for 30 days and daily injections of 100 μg of Decapeptyl for 10 days on the expression of mRNA for pituitary LHRH receptor (LHRH-R) and the levels of LHRH-R protein were evaluated in rats. Serum sex steroid concentrations and the weights of the reproductive organs were greatly reduced in all groups treated with analogs, demonstrating an efficient blockade of the pituitary–gonadal axis. Decapeptyl microcapsules elevated serum LH in female rats, but decreased it in male rats. LHRH-R mRNA expression in female pituitaries was reduced to 41% and 56–65% on days 10 and 30, respectively, whereas LHRH-R protein was 64% of control on day 10 and returned to pretreatment levels on day 30. Decapeptyl microcapsules reduced LHRH-R mRNA expression in male pituitaries to 58% on day 30 but not LHRH-R protein. Daily injections of Decapeptyl caused a desensitization of LH responses in female rats, while raising LHRH-R mRNA expression in female rats by 23% and LHRH-R protein levels by 119%. Cetrorelix pamoate reduced serum LH in female rats and diminished LHRH-R mRNA to 30% and 26% and LHRH-R protein to 57% and 48% on days 10 and 30, respectively. Elevated LHRH-R protein levels of ovariectomized rats were reduced after 10-day treatment with Cetrorelix or 100 μg/day Decapeptyl. Thus, changes in the mRNA expression after treatment with Cetrorelix, but not always Decapeptyl, paralleled those of LHRH-R protein. The inhibitory effect of Cetrorelix on serum LH, pituitary LHRH-R mRNA, and LHRH-R protein was greater than that of Decapeptyl.